Главная

Алгебра 7 класс Ю.Н. Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

ГДЗ учебник по алгебрее 7 класс Ю.Н. Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

авторы: , , , .
издательство: "Просвещение" 2013 г.

Раздел:

Номер №778

Упростите:
а)
$(a^2 - 7)(a + 2) - (2a - 1)(a - 14)$
;
б)
$(2 - b)(1 + 2b) + (1 + b)(b^2 - 3b)$
;
в)
$2x^2 - (x - 2y)(2x + y)$
;
г) (m − 3n)(m + 2n) − m(m − n);
д) (a − 2b)(b + 4a) − 7b(a + b);
е)
$(p - q)(p + 3q) - (p^2 + 3q^2)$
.

Решение а

$(a^2 - 7)(a + 2) - (2a - 1)(a - 14) = a^3 + 2a^2 - 7a - 14 - (2a^2 - 28a - a + 14) = a^3 + 2a^2 - 7a - 14 - 2a^2 + 28a + a - 14 = a^3 + 22a - 28$

Решение б

$(2 - b)(1 + 2b) + (1 + b)(b^2 - 3b) = 2 + 4b - b - 2b^2 + b^3 - 3b + b^4 - 3b^2 = b^4 + b^3 - 5b^2 + 2$

Решение в

$2x^2 - (x - 2y)(2x + y) = 2x^2 - (2x^2 + xy - 4xy - 2y^2) = 2x^2 - 2x^2 - xy + 4xy + 2y^2 = 3xy + 2y^2$

Решение г

$(m - 3n)(m + 2n) - m(m - n) = m^2 + 2mn - 3mn - 6n^2 - m^2 + mn = -6n^2$

Решение д

$(a - 2b)(b + 4a) - 7b(a + b) = ab + 4a^2 - 2b^2 - 8ab - 7ab - 7b^2 = 4a^2 - 14ab - 9b^2$

Решение е

$(p - q)(p + 3q) - (p^2 + 3q^2) = p^2 + 3pq - pq - 3q^2 - p^2 - 3q^2 = 2pq - 6q^2$